2002
DOI: 10.1007/bf03345495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cervical lymph node dissection on serum TG and the course of disease in TG-positive, radioactive iodine whole body scan-negative recurrent/persistent papillary thyroid cancer

Abstract: In the management of papillary thyroid cancer (PTC), surgery is indicated for locoregional recurrent/persistent disease. In this study, we examined the effect of such surgery on serum TG and the course of the disease in 21 patients with PTC (mean age 38.5 yr), who after the initial surgery and radioactive iodine (RAI) ablation developed high TG (>10 ng/ml) and negative 123I whole body scan (DxWBS). All patients had neck persistent/recurrent PTC that was confirmed by ultrasound-guided fine needle aspiration. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…The localisation by direct injection of radioactive substance into the lesion is advantageous, but not all lesions are suitable for this procedure due to their anatomic localisations. This problem can be eliminated with pre-operative neck mapping (6). Currently, high resolution USG is being used as a primary technique for the search of regional recurrences of PTC (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localisation by direct injection of radioactive substance into the lesion is advantageous, but not all lesions are suitable for this procedure due to their anatomic localisations. This problem can be eliminated with pre-operative neck mapping (6). Currently, high resolution USG is being used as a primary technique for the search of regional recurrences of PTC (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Micrometastases and residual tumoral tissues must be removed surgically. It has also been demonstrated that the remission of thyroglobulin (Tg) levels after surgery is very frequent (5,6). The treatment continues with radioactive iodine (RAI) ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the clinical significance of minimally detectable Tg levels is unclear, especially if only detected following TSH stimulation (Cooper et al,2009). Seventy per cent of patients with positive Tg and negative diagnostic total body scan remained disease free during 8 years of follow-up (Alzahrani et al, 2002). In addition, benign sources of Tg secretion have been proposed (Zanotti-Fregonara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The GLUT1 1 3 isobutylisonitrile (MIBI) is clinically used [6,7], and its usefulness has been recently revaluated [8,9]. However, the use of 18 F-fl uorodeoxyglucose positron emission tomography ( 18 F-FDG-PET) in thyroid cancer is increasing, because of its superior spatial resolution as compared with SPECT [10][11][12][13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%